Development of Graphical User Interface for Analysing Induction Motor Current Frequency Spectrum - Husaini, Fatin Najihah; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2022)
In this paper, the development of a graphical user interface (GUI) for analysing the induction motor current frequency spectrum by applying the motor current signature analysis (MCSA) method is presented. Conventionally, analysing the current signature can be time-consuming and reduce the efficiency of the analysis work. Due to that, a GUI is developed to allow the engineer to conduct the analysis efficiently whereby many motors can be monitored. The faults that are analysed are broken rotor bars, stator winding faults, static eccentricity, and dynamic eccentricity. The software used to develop the GUI is the MATLAB App Designer, which allows the user to design the layout and specify the programming according to the desired outcome. To verify the GUI workability, the analysis is carried out by using the conventional method whereby the current measurements provided are analysed in MATLAB. Then, the same data is analysed in the GUI developed. The analysis from both MATLAB and GUI was developed to show that there is an occurrence of at least one type of fault in the motors analysed. It shows that the developed graphical user interface works successfully as the results obtained are the same as the results obtained from the conventional method which is from MATLAB. The motor for chilled and condensed water pump 1 experienced a broken rotor bar whereas the motor for chilled and condensed water pump 2 experienced a stator winding fault. This process can be improved by further investigating the motor condition by conducting a physical inspection of the motor that has been suspected to be faulty based on the results.